2015
DOI: 10.1111/ajfs.12112
|View full text |Cite
|
Sign up to set email alerts
|

Non‐interest Income, Profit, and Risk Efficiencies: Evidence from Commercial Banks in China

Abstract: Chinese commercial banks are transforming their activities into more non-interest income businesses under a highly regulated financial system. This paper investigates the effects of this transformation on profit and risk efficiencies. We find that commission and fee income significantly reduce risk efficiency due to the circumvention of the regulation on deposit interest rate and the assumption of risk that should have been borne by customers. In terms of trading income, it significantly reduces profit efficie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(27 citation statements)
references
References 58 publications
(97 reference statements)
0
20
1
Order By: Relevance
“…There have been many studies about increasing non-interest income by measuring the impact of non-interest activities on the performance of commercial banks. Studies supporting the trend of increasing non-interest income of commercial banks will increase bank performance as stated by De Young and Rice (2004) and Bian et al (2015). Research by Alaaeddin et al (2017) showed that non-interest income enhances equity and this has a positive effect on profitability.…”
Section: Introductionmentioning
confidence: 88%
“…There have been many studies about increasing non-interest income by measuring the impact of non-interest activities on the performance of commercial banks. Studies supporting the trend of increasing non-interest income of commercial banks will increase bank performance as stated by De Young and Rice (2004) and Bian et al (2015). Research by Alaaeddin et al (2017) showed that non-interest income enhances equity and this has a positive effect on profitability.…”
Section: Introductionmentioning
confidence: 88%
“…Non-interest income, including commission fee, and trading income, has become an essential part of bank income all over the world, and China is no exception. In fact, due to the abolishment of floor and ceiling of lending and deposit rate and the development of non-bank institutions, traditional deposits accepting and loans lending business will certainly contribute lower profit ratio in Chinese commercial banks (Bian et al 2015).…”
Section: Non-interest Incomementioning
confidence: 99%
“…The China Banking Regulatory Commission, which was established in 2003 to take up the responsibility of regulating the bank industry, publishedThe Guide for Implementing the Basel IIin 2007 (Bian et al 2015). Issued by the Basel Committee on Banking Supervision, the Basel Accord is a set of recommendations of banking regulations.…”
Section: Capital Adequacy Ratiomentioning
confidence: 99%
See 1 more Smart Citation
“…Noninterest income has become a legitimate activity of banks; indeed, according to DeYoung and Rice (2003), such income now makes up 40% of all operating income in the commercial banking industry of the United States. More and more banks are dependent on non-interest income to increase revenue and profit (Bian et al, 2015). The Vietnam banking system is also working to increase its proportion of noninterest income, but its ability to do so is relatively undeveloped.…”
Section: Introductionmentioning
confidence: 99%